Prognostic accuracy of common heart failure scales in patients with dilated cardiomyopathy. (25th November 2020) - Dziewiecka, E; Gliniak, M; Winiarczyk, M; Karapetyan, A; Wisniowska-Smialek, S; Karabinowska, A; Podolec, P; Rubis, P
Abstract: Introduction: The reliable identification of patients with heart failure (HF) and high mortality risk is crucial for treatment optimalization and prognostication, especially in younger population in dilated cardiomyopathy (DCM). However, the profile of DCM patients significantly differs from the general HF population. Therefore, the applicability of commonly used HF prognostic scales may be sub-optimal in DCM. Purpose: Comparison of the prognostic accuracy of common HF prognostic scales in DCM. Methods: Between 2010 and 2018 we analysed 406 DCM in- and outpatients (aged 54±14 years, 76% male, NYHA: 2.5±0.9, symptoms duration: 40±58 months, EF: 26±9%, LVEDd: 66±10mm, NT-proBNP: 3662±7617pg/ml, 10% had ICD, 3.5% had CRT). The mortality risk was assessed by 8 most popular HF prognostic scores. In 2019 information on patients status were gathered after 48±32months. Results: During first month 4 patients (1.0%) died, after 1 year – 19 (6%), 2 years – 32 (11%), 3 years – 42 (18%), 4 years – 52 (27%), 5 years – 59 (40%). BCN and SHFM calculators had the best prognostic ability for 1–5 years mortality (Table 1). Conclusions: Mortality risk of DCM patients during 5 years is high and reaches 40%. BCN and SHFM calculators had the best prognostic ability for 1–5 years mortality. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Department of Scientific Research and Structural Funds of Medical College, Jagiellonian University